Enhancing physical wellbeing of children: awareness on common disease and relevant health care activities - Maulana Akbar Shah @ U Tun Aung, Maulana (2020)
A peaceful family is not automatically happened, it is created with awareness and expectation. Being parents, their expectations are built with careful attention and all possible means and ways. A most common wish of parents is having healthy and happy children in their lives. it is not easy to own such children as “actions speak louder than words”. Parents must attain philosophies generating happy and healthy children that is developing good akhlaq in them and awareness on common disease imperiling their physical growth. This paper will emphasize on the latter, thus common disease either seasonal or sporadic, parents should have known the regular symptoms and general information of such disease. Besides, healthy children are product of careful nurturing since their birth. As parents, significance of awareness on general health problems of the children will guide them to notice possible emergence of health problem in children. Therefore, this paper will explore the characteristics of the most common diseases happen since birth to 6 years old as well as physiognomies of healthy children indicating assurance of good healthy symptoms in the same period. Among all common disease, nutritional aspect, delivery of vaccine, sleep disorder, constipation, pain, fever, cough and infectious disease such as tuberculosis, influenza, hepatitis are the most dangerous diseases. These diseases can be prevented, if early diagnosis which is dependent on awareness of physiognomies these diseases. This research will be conducted through qualitative methodology collecting information from all available sources including exceptional interviews with relevant authority from Health department and hospitals.